Role of erythrocyte sedimentation rate in ischemic stroke as an inflammatory marker of carotid atherosclerosis - Singh, Amit Shankar (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Inflammation mediates a key role in the pathogenesis of atherosclerosis which is an important cause of ischemic stroke. An elevated erythrocyte sedimentation rate (ESR) may, therefore, be a marker of the extent andor intensity of a general atherosclerotic process and thus a marker for advanced atherosclerosis heralding increased risk of arterial thrombosis leading to ischemic stroke. MATERIALS AND METHODS: ESR was calculated in ischemic stroke patients by Westergren's method along with carotid sonography using high resolution 7.5 MHz techniques to find the prevalence of increased carotid intima-media thickness (CIMT) and presence of plaque according to Mannheim Carotid Intima-Media Thickness Consensus. RESULTS: Average value of ESR in all patients was 27.89 ± 9.73 mm/h. A significant association was found between ESR and markers of carotid atherosclerosis, that is, high CIMT of more than 0.8 mm (P < 0.0001) and presence of plaque (P-0.026) in univariate analysis. Also, a significant positive correlation was found between ESR and serum fibrinogen, another inflammatory marker. (r = 0.88, P < 0.0001). CONCLUSION: The extent of inflammation may reflect in part the propensity of atherosclerotic lesions to lead to clinical disease. Study shows the association of ESR with markers of atherosclerosis confirming the strength of the inflammatory response associated with carotid atherosclerosis and might conceivably carry important prognostic information regarding occurrence of such catastrophic events in future.